Catha Edulis Consumption and its Effects on Economic and Social Well-Being in Yemen - Abdulsiddik, Yusep; Afifah, Sarah (Alhurriyah, 2024)
This qualitative study investigates the impact of Catha edulis (qat) consumption on the economic and social well-being in Yemen, employing the Maqashid Syari'ah framework and a review of relevant literature. Based on secondary data from prior research and sources on Maqashid Syari'ah, the study reveals that qat consumption has significant negative effects on Yemeni society. Socially, it leads to diminished productivity, higher unemployment, and strained family relationships. Economically, the expense of qat diverts resources from essential needs, worsening poverty. Additionally, excessive qat use is linked to health issues, such as oral diseases and psychological problems, which further deteriorate societal well-being. The analysis, viewed through the Maqashid Syari'ah perspective which aims to protect and promote the well-being of individuals and society highlights a misalignment between qat’s socio-cultural benefits and Shariah objectives of safeguarding health, wealth, and family integrity. The study concludes with recommendations for policy and community strategies to address the adverse impacts of qat and foster a more comprehensive approach to improving well-being in Yemen